2014
DOI: 10.1097/mpg.0000000000000443
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Term Infant Formulas Containing High sn‐2 Palmitate With and Without Oligofructose on Stool Composition, Stool Characteristics, and Bifidogenicity

Abstract: Objectives:Levels of stool fatty acid soaps and beneficial bacteria differ between formula-fed and breast-fed infants; addition of specific formula ingredients may reduce these differences. This study evaluated the effects of a term infant formula containing high sn-2 palmitate term infant formula (sn-2) or an identical formula supplemented with oligofructose (OF) at 2 concentrations (sn-2+3 g/L OF, sn-2+5 g/L OF) on stool composition, stool characteristics, and fecal bifidobacteria.Methods:Healthy, term formu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

19
107
0
8

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 81 publications
(134 citation statements)
references
References 47 publications
19
107
0
8
Order By: Relevance
“…However, we did not discriminate between calcium in soaps and “non-soaps”, because of the experimental challenge due to the poor solubility of the soap complex in organic solvents [22] to prove this assumption. Nevertheless, in the present study, fecal calcium was used to estimate the calcium absorption in the rat fed different sn -2 PA diets as previously reported in other studies [17, 23] and our results indicate a positive correlation between dietary sn -2 PA level and calcium absorption. This observation is in agreement with the finding by previous reports [1, 28], in which the authors found that fecal calcium excretion of preterm infants fed high sn -2 PA formula was significantly lower compared with infants fed low sn -2 PA formula.…”
Section: Resultssupporting
confidence: 71%
See 1 more Smart Citation
“…However, we did not discriminate between calcium in soaps and “non-soaps”, because of the experimental challenge due to the poor solubility of the soap complex in organic solvents [22] to prove this assumption. Nevertheless, in the present study, fecal calcium was used to estimate the calcium absorption in the rat fed different sn -2 PA diets as previously reported in other studies [17, 23] and our results indicate a positive correlation between dietary sn -2 PA level and calcium absorption. This observation is in agreement with the finding by previous reports [1, 28], in which the authors found that fecal calcium excretion of preterm infants fed high sn -2 PA formula was significantly lower compared with infants fed low sn -2 PA formula.…”
Section: Resultssupporting
confidence: 71%
“…But little is known if the structure of triacylglycerols is important for altering the intestinal microbiota composition. Although previous studies demonstrated that high percentage of sn -2 PA structured triacylglycerols in infant formula promoted beneficial gut microbiota, such as Lactobacillus and Bifidobacterium , in stool compared with low percentage of sn -2 PA structured triacylglycerols using a culture-dependent technique [16] and fluorescent in situ hybridization (FISH) technique [17]. However, the conclusions are not representative for most bacterial species in the gut.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, no cause and effect relationship could be established by the Panel previously between the feeding of formula high in sn-2 palmitate and stool consistency (EFSA NDA Panel, 2014d). The study by Yao et al (2014), which was published after the opinion of the Panel, reported a significantly higher percentage of mushy soft stools and a significantly lower percentage of formed stools in the group consuming formula high in sn-2 palmitate than in controls. However, results from the pre-planned analyses on the average stool consistency scores between groups and on the percentage of stools in the other stool consistency categories (in total five) were not reported.…”
Section: Molecular Speciation Of Fatty Acidsmentioning
confidence: 99%
“…However, compared with breastfed infants, the FF group stool in the early 3 months of life was less soft (ClinicalTrials.gov Identifier: NCT01157390). sn-2 palmitate, such as increasing beneficial gut flora [15,16] and reducing infant crying [17]. According to our knowledge, this is the first study examining an infant formula with milk fat, prebiotics and structured lipids.…”
Section: Discussionmentioning
confidence: 94%
“…Moreover, it was demonstrated in both preterm and term infants that by increasing the proportion of sn-2 position palmitate in the formula not only that the excretion of palmitate and associated calcium soaps in the stool is reduced and calcium absorption subsequently increased, but also stool hardness is reduced [14]. During the last years, the importance of a fat structure which is similar to that of human milk fat, was further revealed by additional benefits known for human milk, that were demonstrated for infant formula with high sn-2 palmitate, such as increasing beneficial gut flora [15,16] and reducing infant crying [17]. According to our knowledge, this is the first study examining an infant formula with milk fat, prebiotics and structured lipids.…”
Section: Introductionmentioning
confidence: 99%